EFFECT OF ALUMINUM ON PLANT GROWTH, PHOSPORUS AND CALCIUM UPTAKE OF TROPICAL RICE (Oryza sativa), MAIZE (Zea mays), AND SOYBEAN (Glycine max) - D. Nursyamsi; M. Osaki; T. Tadano (Indonesian Journal of Agricultural Science, 2000)
Aluminum toxicity is the most limiting factor to plant growth on acid soils. Structural and functional damages in the root system by Al decrease nutrient uptake and lead to reduce plant growth and mineral deficiency in shoot. Greenhouse experiment was conducted to study the effect of Al on plant growth, and P and Ca uptake of rice, maize, and soybean. The plants were grown in hydroponic solution added with 0, 5, 10, and 30 ppm Al, at pH 4.0. The results showed that relative growth of shoots and roots of upland rice, lowland rice, maize, and soybean decreased with an increase of Al level. However, sometimes the low Al level (5 ppm) stimulated shoot and root growth of some varieties in these species. According to total AlRG30 values, which is Al concentration in solution when relative growth decreased to 50%, Al tolerance of species was in order of barley < maize < soybean < lowland rice < upland rice. For maize, Al tolerance was in the order of Arjuna < Kalingga < P 3540 < SA 5 < SA 4 < PM 95 A < SA 3 < Antasena; for soybean was Wilis < INPS < Galunggung < Kerinci < Kitamusume; for lowland rice was RD 23 < Kapuas < Cisadane < KDML 105 < IR 66 < RD 13, and for upland rice was Dodokan < JAC165 < Cirata < Orizyca sabana 6 < Danau Tempe < Laut Tawar. Based on the rank of Al tolerance, rice was the useful crop to be planted in acid soils. Antasena (maize), Kitamusume ( soybean ), RD 13 (lowland rice), and Laut Tawar (upland rice) were also recommended for acid soils. P and Ca concentration in shoots and roots commonly decreased with an increase of Al level. However, the low Al level stimulated absorption of P and Ca concentrations in shoots and roots.